Comparative Study Of Outpatient Patient Satisfaction General And Companies In Mcu Polyclinic of Rsud Sultan Imanuddin Pangkalan Bun - Rahaju Ningtyas; Rahaju Wiludjeng; Nerlisa Nerlisa (International Journal of Health and Pharmaceutical (IJHP), 2021)
The quality of health services is reflected in the level of patient satisfaction. Thestandard of living of the community affects the demands of society on the quality ofhealth. Outpatient services at Sultan Imannudin Hospital are divided into twoaccording to the payment method, namely insurance and general patients. Thepurpose of this study was to determine the comparative satisfaction of general andcorporate outpatients in the MCU Polyclinic at Sultan Imanuddin Hospital.Thisstudy uses a non-experimental method: comparative. namely to determine thedifference in outpatient satisfaction with company and general guarantees.Theresults of the study are based on the Wilcoxon sigred rank test with a value of p =0.000 <0.05, which means that there is a significant difference between generaloutpatient satisfaction and company outpatient satisfaction. The level of generalpatient satisfaction is satisfied, while the company's patient satisfaction level is verysatisfied. This is due to the financing factor. The satisfaction level of outpatientcompanies is very satisfied because from a financial perspective they don't need tothink about it anymore. Insured patients (company patients) only receive theservices provided to them. While general patients feel satisfied because they have topay medical fees, so the demands on the quality of service are also high.It issuggested that the assessment of the level of patient satisfaction is carried outregularly and periodically as input for making policies in improving service quality,especially focused on the dimension of reliability (reliability).